Developing the ‘Life Threads’ approach to support families after traumatic brain injury in UK community settings: protocol for a qualitative prefeasibility study - Caroline Ellis-Hill; Fergus Gracey; Mark Holloway; Charlotte Jane Whiffin; Alyson Norman; Morag Lee; Parmjeet Kaur Singh; Jo Clark-Wilson; Audrey Daisley; Natasha Yasmin Felles; Sara Rose (BMJ Open)
Introduction Traumatic brain injury (TBI) brings about inevitable and significant changes for family members. Mental health effects for family members are well documented but there are significant gaps in support options across services. Here, we describe our protocol for a study that seeks to investigate the potential for a narrative, creative approach, the ‘Life Threads’ approach, as a low intensity, accessible means of support that can be applied across service contexts.Methods We will recruit 20 family members of someone who sustained a TBI from services in an area of the UK with a diverse demographic. Family members will be provided with the ‘Life Threads’ approach materials and guided in their use. The study is planned to run from March 2023 to July 2024.Analysis Collection of data on potential usefulness, feasibility and acceptability will be through focus groups and individual interviews. Transcripts will be analysed using reflexive thematic analysis, conducted within a relativist, constructivist orientation.Ethics and dissemination Ethical approvals have been sought and gained (Nottingham 1 Research Ethics Committee, 23/EM/0185, 4 September 2023), and the study has been registered with ISRCTN. As a research team, we are guided by our own personal, professional and research experiences of TBI which we will consider reflexively throughout the research process. Results will be disseminated in collaboration with our patient and public involvement group through open peer-reviewed journal publication and scientific conference, with lay summaries shared via recruitment sites.Trial registration number ISRCTN17392794.